A natural antipredation experiment: predator control and reduced sea ice increases colony size in a long‐lived duck. Issue 10 (1st September 2013) - Hanssen, Sveinn A.; Moe, Børge; Bårdsen, Bård‐Jørgen; Hanssen, Frank; Gabrielsen, Geir W.
Abstract Anthropogenic impact on the environment and wildlife are multifaceted and far‐reaching. On a smaller scale, controlling for predators has been increasing the yield from local natural prey resources. Globally, human‐induced global warming is expected to impose severe negative effects on ecosystems, an effect that is expected to be even more pronounced in the scarcely populated northern latitudes. The clearest indication of a changing Arctic climate is an increase in both air and ocean temperatures leading to reduced sea ice distribution. Population viability is for long‐lived species dependent on adult survival and recruitment. Predation is the main mortality cause in many bird populations, and egg predation is considered the main cause of reproductive failure in many birds. To assess the effect of predation and climate, we compared population time series from a natural experiment where a trapper/down collector has been licensed to actively protect breeding common eiders Somateria mollissima (a large seaduck) by shooting/chasing egg predators, with time series from another eider colony located within a nature reserve with no manipulation of egg predators. We found that actively limiting predator activity led to an increase in the population growth rate and carrying capacity with a factor of 3–4 compared to that found in the control population. We also found that population numbers were higher in years with reduced concentration of spring sea ice. We conclude that there was a large positive impact of human limitation of egg predators, and that this lead to higher population growth rate and a large increase in size of the breeding colony. We also report a positive effect of warming climate in the high arctic as reduced sea‐ice concentrations was associated with higher numbers of breeding birds.